ITERATIVITY AS BASIC OF THE MULTIPLICITY SEMANTICS OF ACTION AND A TYPOLOGICAL VARIETY OF THE QUANTITATIVELY PARTIBLE OF ACTION - Vakaliuk, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the article defined content of the concept iterative on the basis of the concept of the semantic structure of the interval category; the functional semantical peculiarities of the suffixes -a- (-я-), -ва-, -ува-(-юва-), -и-, і-, -от-i,(-от-a) as means of expressing of iterativity in modern Ukrainian language are examined; the problem of interdepence of semantic and functional morphemes in the structure of iterative verbs is considered.